2016
DOI: 10.1075/lab.6.6.01lil
|View full text |Cite
|
Sign up to set email alerts
|

The development of bimodal bilingualism

Abstract: A wide range of linguistic phenomena contribute to our understanding of the architecture of the human linguistic system. In this paper we present a proposal dubbed Language Synthesis to capture bilingual phenomena including code-switching and ‘transfer’ as automatic consequences of the addition of a second language, using basic concepts of Minimalism and Distributed Morphology. Bimodal bilinguals, who use a sign language and a spoken language, provide a new type of evidence regarding possible bilingual phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…As for bimodal bilingualism, research shows that crosslinguistic influence is observed in structures not predicted by such conditions (Lillo-Martin et al, 2010), and findings for the structures that satisfy these two conditions run counter to predictions (Koulidobrova, 2012, 2016). Recently, Language Synthesis (Koulidobrova, 2012, 2016; Lillo-Martin et al, 2012, 2014, 2016) has been proposed to account for the various language interaction effects observed in bimodal bilingualism (see the next section). The proposal is based on MacSwan's (2000, 2005) accounts for code-switching, in which he argues for one computational system with separate lexicons and separate Phonetic Forms (PFs) for different languages.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As for bimodal bilingualism, research shows that crosslinguistic influence is observed in structures not predicted by such conditions (Lillo-Martin et al, 2010), and findings for the structures that satisfy these two conditions run counter to predictions (Koulidobrova, 2012, 2016). Recently, Language Synthesis (Koulidobrova, 2012, 2016; Lillo-Martin et al, 2012, 2014, 2016) has been proposed to account for the various language interaction effects observed in bimodal bilingualism (see the next section). The proposal is based on MacSwan's (2000, 2005) accounts for code-switching, in which he argues for one computational system with separate lexicons and separate Phonetic Forms (PFs) for different languages.…”
Section: Introductionmentioning
confidence: 99%
“…We will first summarize the word order issues that have been documented in bimodal bilingual acquisition of a number of language pairs. Then, we introduce Language Synthesis, recently proposed to account for language interaction effects such as code blending, code switching, as well as crosslingusitic influence and transfer (Lillo-Martin et al, 2016). Based on these discussions, we compare the verb root and word order issues with the relevant constructions between Cantonese and HKSL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatedly, another relevant factor in language variation across our participants had to do with their professional involvement with Deaf people, since one of the participants is a professional sign language interpreter. This research is the first step in our understanding of language variation in bimodal bilinguals; additional research considers the ways that bimodal bilinguals combine their languages in the code-blending phenomenon, which provides further means to investigate the nature of heritage bimodal bilingualism Lillo-Martin et al 2016). …”
Section: Discussionmentioning
confidence: 99%